”Det är världens roligaste jobb” - Att främja delaktighet och musikalisk kunskapsutveckling i anpassad grundskola ur ett musiklärarperspektiv - Strandberg,Tilda; Hult,Vilma; Westerdahl,David (2025)
This study investigates how five music teachers that are, or have been, working in Swedish compulsory school for pupils with intellectual disabilities describe how they are working with development of musical knowledge, inclusion and goal attainment. The study is conducted by using semistructured interviews and is grounded in social constructivism as its scientific theoretical framework. The selection of research topic is rooted in a curiosity about how we, as future teachers, can implement individual adaption in music education. To obtain examples of how this is manifested in practice the study also investigates which methods and strategies the music teachers are using. The results show that the informants facilitate the development of musical knowledge by maintaining high expectations for their pupils and not viewing intellectual disabilities as an obstacle to learning. Further examples addressed in this study for creating conditions for developing musical knowledge and inclusion are clear structure, KASAM, delaktighetsmodellen (theoretic model for inclusion), salutogenic approach, individual adaption, relational work and usage of methods that approaches theory through practice. Through the results and previous research, it is shown that there is much to be gained from the experience and knowledge possessed by the music teachers in compulsory school for pupils with intellectual disabilities, where knowledge of various methods forms an essential component of their professional competence. It also becomes evident that participation, which is a central concept in the governing documents for the compulsory school for pupils with intellectual disabilities, can be interpreted in various ways and may be linked to inclusion.
Keywords: Anpassad grundskola; Musikundervisning; Intellektuell funktionsnedsättning; Individanpassning; Deltagande; Delaktighet; Compulsory School for Pupils with Intellectual Disabilities; Music education; Individual adaption; Special education; Participation; Inclusion; Utbildningsvetenskap; Musikpedagogik; Educational Science